Tracing of Afferent Connections in the Zebrafish Cerebellum Using Recombinant Rabies Virus - Dohaku, Ryuji; Yamaguchi, Masahiro; Yamamoto, Naoyuki; Shimizu, Takashi; Osakada, Fumitaka; Hibi, Masahiko (Frontiers in Neural Circuits, 2019)
The cerebellum is involved in some forms of motor coordination and learning, and in cognitive and emotional functions. To elucidate the functions of the cerebellum, it is important to unravel the detailed connections of the cerebellar neurons. Although the cerebellar neural circuit structure is generally conserved among vertebrates, it is not clear whether the cerebellum receives and processes the same or similar information in different vertebrate species. Here, we performed monosynaptic retrograde tracing with recombinant rabies viruses (RV) to identify the afferent connections of the zebrafish cerebellar neurons. We used a G-deleted RV that expressed GFP. The virus was also pseudotyped with EnvA, an envelope protein of avian sarcoma and leucosis virus (ALSV-A). For the specific infection of cerebellar neurons, we expressed the RV glycoprotein (G) gene and the envelope protein TVA, which is the receptor for EnvA, in Purkinje cells (PCs) or granule cells (GCs), using the promoter for aldolase Ca (aldoca) or cerebellin 12 (cbln12), respectively. When the virus infected PCs in the aldoca line, GFP was detected in the PCs’ presynaptic neurons, including GCs and neurons in the inferior olivary nuclei (IOs), which send climbing fibers (CFs). These observations validated the RV tracing method in zebrafish. When the virus infected GCs in the cbln12 line, GFP was again detected in their presynaptic neurons, including neurons in the pretectal nuclei, the nucleus lateralis valvulae (NLV), the central gray (CG), the medial octavolateralis nucleus (MON), and the descending octaval nucleus (DON). GFP was not observed in these neurons when the virus infected PCs in the aldoca line. These precerebellar neurons generally agree with those reported for other teleost species and are at least partly conserved with those in mammals. Our results demonstrate that the RV system can be used for connectome analyses in zebrafish, and provide fundamental information about the cerebellar neural circuits, which will be valuable for elucidating the functions of cerebellar neural circuits in zebrafish.